Distinguished Manglorean catholics.(1800-2000) - LOBO (Michael) (Mangalore. Michael Lobo., 2000)
A Historico-Biographical survey of the Mangalorean Catholic Community
Keywords: Manglorean DK; South Kanara /South Canara